Klasifikasi Lokasi Indoor atau Outdoor berdasarkan Pengaruh Cahaya Terhadap Alat Tracking GPS pada Hewan menggunakan Metode K-Nearest Neighbor - Samuel Lamhot Ladd Palmer Simarmata; Dahnial Syauqy; Hurriyatul Fitriyah (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Pets, animals maintained by humans, are exceedingly required to look after and take care by the owners. The development of science and technology has been sustaining to apply these purposes by the existence of the tracking devices which can be inserted to the pets. The classification of indoor and outdoor location based on the effect of the lights is conducted in this research to control the data sending from the location of the pets. K-Nearest Neighbor algorithm is required to support the system in determining the location classification of pets. The implementation of the systems is based on the two prototypes; master and slave. Slave system is to record the value of the lights and the coordinates of the pets. Besides, the master system is to receive the data, process the K-Nearest Neighbor algorithm, and connect to the laptop in order to show the output data. The accuracy obtained from the indoor and outdoor classification in this study was 98%. The test of K-value in this method was applied with the K-value of K=3, K=7 and K=9.